Peran Akademisi Dalam Pencegahan Covid-19 Dengan Pemberdayaan Masyarakat Dalam Mewujudkan Perilaku Sehat - Rahmi Susanti; Aghnia Sabrina; Lisa Ariana Putri; Tahsya Erika; Laila Citra Sandi (Training & Research Institute - Jeramba Ilmu Sukses, 2020)
WHO declared Covid-19 on March 12, 2020 as a pandemic. Indonesia is one of the countries with a high number of confirmed cases, namely until December 10, 2020, there were 598,933 confirmed Covid-19 cases. Covid-19 is a virus that attacks the respiratory system with symptoms of fever, cough, runny nose, sore throat, shortness of breath, fatigue and lethargy. The incubation period for Covid-19 ranges from 1 to 14 days. Covid-19 can spread through the air, direct contact with sufferers, droplets, fomite, blood, and transmission from animals to humans. This activity aims to provide education regarding the prevention of the spread of Covid-19 in the community in the RT.45 Loa Ipuh Village area. This activity was carried out for 3 days, starting on November 21-23, 2020, in the form of actions in the form of installing banners, distributing posters and masks and distributing educational videos regarding the prevention of the spread of Covid-19 and management if someone was detected by Covid-19. This activity received a good reception by the community, this was shown by the participation of the community in the implementation of the distribution of posters and masks, as well as the installation of banners in the RT.45 Loa Ipuh Village. With this activity, it is hoped that it can increase knowledge and increase awareness of the RT.45 community about the importance of preventing the spread of Covid-19.